ANALISIS KINERJA LEMBAGA PEMASYARAKATAN DALAM PEMBINAAN TERHADAP ANAK DIDIK PEMASYARAKATAN DI PASIR PENGARAIAN TAHUN 2011-2013 - Lusy Febriani; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Performance is the result of work carried out with the expected value. The work is targeted to be achieved by an organization in order to achieve the goal. The work that is to be achieved not only describe the end point of the planning work, but also shows the work of organizing the system, filling job, leadership style and employee control all these are factors supporting the work of achieving the desired result by a unit of work.This study is a descriptive study using a qualitative approach as a tool of analysis. The research was conducted in the Pasir Pengaraian, Rokan Hulu with a focus on Performance Analysis Penitentiary in the Guidance for Correctional Learners in Prison Class II B Pasir Pengaraian along with factors that constrain the development process. The theory used is the theory of relative or destination (Doeltheorien). The technique used in data collection were interviews, observation and documentation. After conducting research hence writers can conclude that the process of improving that has not been the protege correctional institution in class II a correctional institution b Pasir pengaraian students correctional institution and the difficult to produce guidance that effective , efficient , and successfully to . Factors that most affect the implementation of guidance of students in a correctional institution not maximum is the capacity of inhabitant of lapas excessive ( over the capacity of ) , funds , lapas officers , as well as experts .Keywords: Performance, Development, Correctional Learners.